Towards optimising routing overhead in wireless multi-hop networks. (2015) - Javaid, N.; Bibi, A.; Mohammad, S.N.; Khan, Z.A.; Alrajeh, N.
In this paper, we select three most widely used reactive protocols; ad-hoc on-demand distance vector (AODV), dynamic source routing (DSR) and dynamic MANET on-demand (DYMO), and model their energy and time consumption costs of expanding ring search (ERS) algorithm in wireless multi-hop networks (WMhNs). A novel contribution of this work is tuning the route discovery and route maintenance parameters of the chosen protocols to minimise routing overhead. For analytical comparison, we simulate default and enhanced versions of these protocols using NS-2. From modelling and analytical comparison, we deduce that adjusting time-to-live (TTL) values in search sets of ERS algorithm with respective waiting time is more useful for reducing bandwidth and locating time in chosen protocols. Moreover, for reliable transmission and efficient performance, reactive protocols need immediate detection of link breakage along with quick repairement strategies for re-establishment of routes such as local link repair (LLR) and packet salvaging (PS).